Ethical Issues in Online News Reporting in Nigeria - Fiki, Maigida; Idi, Shadrach (Asian Journal of Science, Technology, Engineering, and Art, 2025)
The central narrative guiding ethical concerns in Nigeria's media landscape is the alarming rise of fake news, hate speech, questionable source credibility, quackery, and weak internal censorship—practices that contribute significantly to ethical lapses across online journalism platforms. In an era increasingly dominated by sensationalism and disinformation, there is diminishing emphasis on ethically sound and balanced reporting, which traditionally underpins objective journalism. This study investigates the ethical challenges associated with online reporting practices in Nigeria, with a specific focus on the proliferation of fake news across digital media platforms. Anchored in the Social Responsibility Theory, the research employs focus group discussions and key informant interviews for data collection. A systematic sampling technique was used to select 5,944 registered journalists, media scholars, and members of the Nigerian Union of Journalists’ ethics committee from all six geo-political zones. Data were analyzed through detailed thematic probes and discussions. Key findings reveal a significant lack of comprehensive understanding of media laws among practitioners, many of whom are unaware of the legal implications tied to their professional responsibilities. The study highlights the critical need for clearly defined editorial policies to enhance source credibility and mitigate the spread of fake news and hate speech. Furthermore, ethical non-compliance is largely driven by the presence of untrained individuals posing as media influencers across various internet-based platforms. The study recommends deliberate efforts to improve awareness and enforcement of media laws, the establishment of a strong regulatory framework by both government and the Nigerian Union of Journalists, and ongoing training and retraining programs for digital media practitioners to uphold ethical journalism standards.